PENGGUNAAN MEDIA KOMUNIKASI DI SLB NEGERI SALAKAN: Studi Media Richness Theory dalam Kegiatan Belajar Mengajar pada Siswa Tunagrahita Selama Masa Pandemi COVID-19 - Haidar, Nur; Diasa, Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2022)
The purpose of this study was to determine the communicate media used at SLB Negeri Salakan in teaching and learning activities for mentally retarded students during the Covid-19 pandemic. This type of research is a case study using purposive sampling technique in determining informants. In this study, there were five people who were appointed as informants, and the data collection techniques used were observation and in depth interviews, which used interview guidelines as data collection media.The results showed that teaching and learning activities in SLB Negeri Salakan for children with mental retardation, there were four types of media used, the first media used images printed on paper, the second media used the Secil application, the third media used YouTube videos, and the fourth media used music/ song. Of the four media used, two of them are internet based, the media used mean is Secil application learning and YouTube videos. Referring to the media richness theory which looks at the four criteria according to the results of research in the field that image media, Secil application learning, YouTube video, and music media have the ability to convey cues, promptness in giving feedback, diversity of language used, and ability to focus.